PENGARUH KOMPETENSI DAN DISIPIN KERJA TERHADAP KEPUASAN KERJA PADA RUMAH SAKIT MUHAMMADIYAH PALEMBANG - Ayu Zahirah; Zuraidah Siregar; Sugeng Mianto Fane (Jurnal Manajemen, 2020)
This study aims to analyze the influence of competence and discipline work against satisfaction work in hospital.Muhammadiyah Palembang. Population in this research is nurse hospital RS.Muhammadiyah Palembang. Sample in this research uses the method proportional random sampling, with 146 nurses. Data analysis was conducted using SPSS. The research results show that competence have had a positive impact on satisfaction work nurse in hospital RS. Muhammadiyah Palembang, while discipline of a work as partial have had a positive impact and significant impact on satisfaction work nurse hospital RS. Muhammadiyah Palembang. Variable competence and discipline work against satisfaction work, show competence influential are more dominant of 10,424 than discipline work is only 2,481.